How Supervisory Support Shapes Work Life Balance Satisfaction of Employees” - Singh, Neha; Brahmbhatt, Mamta (International Journal of Psychosocial Rehabilitation, 2020)
The objective of this study is to understand the role of Supervisory Support on Work Life Balance Satisfaction of the employees. This study also aims to determine the relation between Work Life Balance Satisfaction and Job Satisfaction levels and later with Employee Commitment levels. Simple random sampling method was used for data collection and 460 employees from Ahmedabad city were contacted via structured Questionnaire. A total of 247 responses were received (response rate was 53.6%). Data was analyzed using Simple Linear Regression. It was found that Supervisory Support is a strong predictor of Work Life Balance Satisfaction levels of the employees. The later impacts Job Satisfaction to a greater extent and in turn Job Satisfaction has an influence on Employee Commitment levels.